To study relation of haemoglobin level and platelet count - Berad, Akshay Suryabhan; Gurbani, Naresh (International Journal of Research in Medical Sciences, 2016)
Background: The relationship between haemoglobin level and platelet count was carried among 116 volunteer with respect to differences between platelet count within haemoglobin (gm%) level within platelet count. Methods: Blood samples were collected into EDTA anticoagulant bulbs for both platelet count and haemoglobin level from healthy subjects. Results: Statistical analysis showed significant differences (p<0.05) between haemoglobin level that fell within platelet count 1.5 to 2.5 lacs/mm3 as (11.7±1.62) and haemoglobin level that fell within platelet count 2.51-4 lacs/mm3 as (9.1±2.40). statistical analysis also show a significant difference (p<0.05) between platelet count that fell within the haemoglobin level less than 11 gm% as (2.62±0.86) and platelet count that fell within haemoglobin level of 11-16 gm% as (2.11±0.42). Conclusions: The above results indicate that there is a relationship between low and high level of haemoglobin on platelet count and vice versa.